2014
DOI: 10.4103/2229-516x.136789
|View full text |Cite
|
Sign up to set email alerts
|

To compare the efficacy and safety of fixed dose combination of thiocolchicoside and aceclofenac versus chlorzoxazone, aceclofenac and paracetamol in patients with acute lower backache associated with muscle spasm

Abstract: Background:The fixed dose combinations (FDCs) of muscle relaxants, non-steroidal anti-inflammatory drugs and paracetamol are commonly prescribed in the treatment of acute lower backache.Aim:The present study was undertaken with the aim of comparing the efficacy and safety of FDCs of thiocolchicoside and aceclofenac versus chlorzoxazone, aceclofenac and paracetamol in patients with acute lower backache associated with muscle spasm.Materials and Methods:A total of 100 patients between ages range from 18 and 55 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Nielsen et al 20 demonstrated no reduction in acute postoperative pain after a single 500 mg administration of chlorzoxazone after spine surgery for patients with moderate-to-severe pain, which is in line with present study. Furthermore a study by Kumar et al 29 investigated the efficacy of the combination of thiocolchicoside and aceclofenac versus…”
Section: Chlorzoxazone For Postoperative Pain Managementmentioning
confidence: 99%
“…Nielsen et al 20 demonstrated no reduction in acute postoperative pain after a single 500 mg administration of chlorzoxazone after spine surgery for patients with moderate-to-severe pain, which is in line with present study. Furthermore a study by Kumar et al 29 investigated the efficacy of the combination of thiocolchicoside and aceclofenac versus…”
Section: Chlorzoxazone For Postoperative Pain Managementmentioning
confidence: 99%
“…Muscle relaxants such as thiocolchicoside, a competitive gamma-aminobutyric acid (GABA) receptor antagonist, are a good treatment option for patients with muscle spasm-associated low back pain [ 38 ]. Similarly, tolperisone, a piperidine derivative and centrally acting muscle relaxant, is an effective option in the presence of skeletal muscle spasm [ 39 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Зачастую для получения максимального эффекта требуются высокие дозы НПВП и миорелаксантов, что увеличивает риск возникновения побочных эффектов со стороны желудочно-кишечного тракта, способствует резкому снижению/повышению артериального давления (АД), появлению выраженного седативного эффекта, спутанности сознания, головокружения, слабости и нарушения координации, ухудшению когнитивных функций [20]. В то же время правильная с позиции фармакологии комбинация имеет преимущества по сравнению с монопрепаратами, особенно у пожилых пациентов, у которых может быть недостаточный или «извращенный» ответ на отдельное ЛС, особенно при наличии артериальной гипертензии [19].…”
Section: Introductionunclassified